EFFECT OF DIFFERENT LIGHT TYPES AND EXPOSURE DURATIONS ON STOMATAL CHARACTERISTICS IN TWO CULTIVARS OF CARNATION (Dianthus caryophyllus L.) - Mohammed, Layla; Yousif Edo, Nashwan; Ali, Sajid (Science Journal of University of Zakho, 2025)
A study was conducted to examine the effects of different light types, colors, and exposure durations on the morphological and stomatal characteristics of two carnation (Dianthus caryophyllus) cultivars, Ormea and Moonlight, cultivated under controlled greenhouse conditions, during the period of (2024 - 2025) at the College of Agricultural Engineering Sciences, University of Duhok, to understanding how Light quality and photoperiod play a crucial role in regulating stomatal density, size, and function, which are vital for key physiological processes such as transpiration and photosynthesis. The results indicate that specific light treatments significantly influence both morphological traits and stomatal parameters. The highest leaf number, leaf length, and leaf area per plant, were measured under 14-hour incandescent lighting (42.872 leaves/plant, 13.050 cm, and 25.801 cm2), respectively, followed by 14h LED-mix (39.37leaves/plant, 12.020 cm and 24.218cm2), respectively. Similarly, the longest leaf observed on the Ormea cultivar (12.336 cm) when exposed to 14 hours of incandescent light significantly outperformed other treatments. While the results of the interaction between cultivar and light on stomatal density and number showed that the Moonlight cultivar could achieve higher stomatal densities and stomatal numbers when exposed to 14 hours of incandescent. On the other hand, the Ormea and Moonlight cultivars showed the highest significant increase in stomatal densities (96.482 and 95.587) in the lower epidermis when exposed to 14 hours of incandescent lights. In the Ormea cultivar, growing under incandescent light for 14h caused a notable increase in both stomatal length and width (24.978 and 13.389 µm), followed by stomatal length and width (24.533 and 13.067 µm), respectively, under LED-mix for 14h